COMPARISON STUDY OF SAFETY FACTOR AND STRENGTH FACTOR IN NUMERICAL MODELING FOR SLOPE STABILITY ANALYSIS BASED ON MOHR-COULOMB CRITERIA - Adhiwijna, Padmanatha
Slope stability is a critical factor in open-pit mining operations. To assess slope stability, the commonly used indicator is the Safety Factor (FoS) to determine slope strength. However, in software utilizing the Finite Element Method (FEM), the term Strength Factor (SF) is more frequently encountered. This study aims to compare FoS and SF in slope stability analysis using numerical modeling based on the Mohr- Coulomb criterion. The results show a similarity between FoS and SF values in determining slope stability, where the FoS and SF values at the specified points tend to be equivalent under disturbed conditions. However, the comparison also reveals that most FoS and SF values can significantly differ under stress conditions approaching in situ stress.